An improved QOS in the architecture, model and huge traffic of multi-media applications under high speed wireless campus network - Yalli, Jameel Shehu; Abdul Latif, Suhaimi; Hassan Abdalla Hashim, Aisha; Alam, Md Korshed (Asian Research Publishing Network (ARPN), 2014)
Multi-media applications are in high demand by many users. Many telecommunication companies are into the business of providing these applications such as the Voice over Internet Protocol (VOIP) and video conferencing. Users often become unsatisfied with the services they receive from their service providers. This is as a result of lack of guaranteed QoS in today’s high speed wireless campus network (WCN). The internet is the main platform on which these applications run on and therefore all credits and blame goes to the designers of the internet. Several researchers have worked towards improving the QoS of these applications and they have contributed immensely to it. However, this work reviewed previous works and comes up with a new methodology that ensures QoS of multi-media applications in the high speed Wireless Local Area Network (WLAN). The design and simulation shows a great improvement in the overall network performance. This is measured in terms of three network parameters, viz: average end-to-end delay, average jitter and throughput. We introduce a mapping technique with which we assign the highest of all priorities to the multi-media traffic. Firstly there is a mapping between the Quality of Service Class Identifier (QCI) to the Differentiated Service Code Points (DSCP), where each of it is a QoS giver. Then, the QCI/DSCP is mapped to our multi-media traffics. Our design has already excelled the default design by achieving lower end-to-end delay, regular jitter and higher throughput. We then incorporate a huge traffic in our scenario and measured the performance again; our new mechanism achieves the best result compared to all the similar scenarios with huge traffic. The overall performance of the network is improved with no less than 50%.